SEJARAH DAN PERUBAHAN PESANTREN DI ACEH - Marzuki Marzuki (Millah: Journal of Religious Studies, 2011)
Pesantren has a long history, since before independence and still exist today. Zamakhsary Dhofier in his book "Tradisi Pesantren" indicates that the boarding school kept changing his way, reinforced by the statement of HAR Gibb and Snouck Hurgronjo about such changes. Actually what is happening in the development indicated boarding school, both pesantren in Java and outside Java, such as in Aceh. This change has long occurred in Java, even since the Dutch era, but in Aceh, the change has just occurred in recent years. Pesantren has transformed himself from the agency / institution that had shaped Meunasah (musalla), balee (hall) which traditionally becomes a nuanced Madrasah education by adopting modern, up to recent developments in Higher Education has been established in the